2013
DOI: 10.2215/cjn.03510413
|View full text |Cite
|
Sign up to set email alerts
|

Association of Elevated Urinary Concentration of Renin-Angiotensin System Components and Severe AKI

Abstract: SummaryBackground Prognostic biomarkers that predict the severity of AKI at an early time point are needed. Urinary angiotensinogen was recently identified as a prognostic AKI biomarker. The study hypothesis is that urinary renin could also predict AKI severity and that in combination angiotensinogen and renin would be a strong predictor of prognosis at the time of AKI diagnosis.Design, setting, participants, & measurements In this multicenter, retrospective cohort study, urine was obtained from 204 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 38 publications
(38 reference statements)
1
32
0
1
Order By: Relevance
“…Of note, uAGT outperformed the other three biomarkers. This study is also important, because it confirms previous observations that uAGT is increased in the setting of AKI and can predict its progression to higher stages or death after cardiac surgery (8,9) or in acute decompensated heart failure (10).…”
supporting
confidence: 85%
“…Of note, uAGT outperformed the other three biomarkers. This study is also important, because it confirms previous observations that uAGT is increased in the setting of AKI and can predict its progression to higher stages or death after cardiac surgery (8,9) or in acute decompensated heart failure (10).…”
supporting
confidence: 85%
“…Thus, to what degree urinary renin yields information independent from the circulating RAS remains to be determined. Alge et al (4) recently reported that urinary renin, together with urinary angiotensinogen, associates with AKI after cardiac surgery. Their urinary renin levels were measured with the Quantikine Renin ELISA Kit and exceeded published plasma renin levels (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Given the noncalibrated standard of this ELISA, it is not surprising that Alge et al (4), when using this kit, obtained urinary renin levels that are far above the normal range in plasma (11) and, most likely, even above the plasma levels in patients who developed AKI after cardiac surgery. It should be noted that plasma renin values were not reported in their study but that their highest urinary total renin levels (2894 pg/ml) exceed the plasma levels of total renin measured in heart failure patients treated with RAS blockers (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations